Differences in the Between–Person and Within–Person Structures of Affect Are A Matter of Degree. Issue 1 (January 2015) - Brose, Annette; Voelkle, Manuel C.; Lövdén, Martin; Lindenberger, Ulman; Schmiedek, Florian
This study tested whether the structure of affect observed on the basis of between–person (BP) differences is equivalent to the affect structures that organize the variability of affective states within persons (WP) over time. Further aims were to identify individual differences in the degree of divergence between the WP and BP structure and examine its association to dispositional and contextual variables (neuroticism, extraversion, well–being and stress). In 100 daily sessions, 101 younger adults rated their mood on the Positive and Negative Affect Schedule. Variability of five negative affect items across time was so low that they were excluded from the analyses. We thus worked with a modified negative affect subscale. WP affect structures diverged reliably from the BP structure, with individual differences in the degree of divergence. Differences in the WP structural characteristics and the degree of divergence could be predicted by well–being and stress. We conclude that BP and WP structures of affect are not equivalent and that BP and WP variation should be considered as distinct phenomena. It would be wrong, for example, to conceive of positive and negative affect as independent at the WP level, as suggested by BP findings. Yet, individual differences in WP structural characteristics are related to stable BP differences, and the degree to which individuals' affect structures diverge from the BP structure can provide important insights into intraindividual functioning. Copyright © 2014 European Association of Personality Psychology